2018
DOI: 10.1111/sji.12671
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of exogenous complement factor H in mice in vivo

Abstract: Factor H is an important regulator of complement activation in plasma and on cell surfaces in both humans and mice. If FH function is compromised, inappropriate complement activation on self-surfaces can have disastrous effects as seen in the kidney diseases atypical haemolytic uremic syndrome (aHUS) and C3 glomerulopathy. As FH constructs have been proposed to be used in treatment for these diseases, we studied the distribution of exogenous FH fragments in mice. Full-length mFH, mFH1-5 and mFH18-20 fragments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
2
1
0
Order By: Relevance
“…These results were broadly in keeping with studies by Koshinen et al. ( 75 ) who looked at the distribution of iodinated full length mFH or mFH1-5 or mFH18-20, although their studies were over a shorter time frame and did not involve mini-FH constructs and showed full-length FH distribution was dependent on C3 fragment deposition. Thus, our data may help to explain the lower half-life of the mini-FH drugs in CFH -/- mice compared to native serum-purified full-length mFH.…”
Section: Discussionsupporting
confidence: 90%
“…These results were broadly in keeping with studies by Koshinen et al. ( 75 ) who looked at the distribution of iodinated full length mFH or mFH1-5 or mFH18-20, although their studies were over a shorter time frame and did not involve mini-FH constructs and showed full-length FH distribution was dependent on C3 fragment deposition. Thus, our data may help to explain the lower half-life of the mini-FH drugs in CFH -/- mice compared to native serum-purified full-length mFH.…”
Section: Discussionsupporting
confidence: 90%
“…The anticipated predominant targeting of CPV-101 to the liver probably reflects clearance by mannose-receptor C-type 1, which is strongly expressed on liver sinoidal endothelial cells and is known to accept GlcNAc-tipped glycans as ligands (65). The excretion data for all three variants were in overall good agreement with the previously published results for sd-FH (66).…”
Section: Discussionsupporting
confidence: 86%
“…Previous works have reported the tagging and imaging of FH analogues, using I-125 labelling ( 32 ) Tc-99m ( 33 ) or optical tags ( 34 ), however, these studies presents limitations in terms of imaging performance (i.e. planar scintigraphy or autoradiography), scope (i.e.…”
Section: Resultsmentioning
confidence: 99%